Successful Management of Acute Respiratory Failure Following Drowning in a Child: A Case Report - Diki Septian; Anggun Pulihana Wilujeng (HM Publisher, 2025)
Background: Drowning is a significant global public health issue, leading to a substantial number of deaths annually, particularly among children. Acute respiratory failure (ARF) is a common and life-threatening complication of drowning, necessitating prompt and effective management. This case report describes the successful management of ARF in a 6-year-old child following a drowning incident. Case presentation: A 6-year-old male child was brought to the emergency department (ED) after being rescued from a river. He was unconscious, cyanotic, and in respiratory distress. Initial assessment revealed a Glasgow Coma Scale (GCS) score of 9, oxygen saturation of 45% on room air, and crackles on lung auscultation. He was immediately intubated and placed on mechanical ventilation. A chest X-ray showed evidence of pneumonia and pulmonary edema. Arterial blood gas analysis confirmed acute hypoxemic respiratory failure. The patient was transferred to the intensive care unit (ICU) and managed with mechanical ventilation, antibiotics, and corticosteroids. He demonstrated gradual improvement in respiratory status and neurological function, leading to successful extubation and eventual discharge with a full recovery. Conclusion: This case highlights the critical role of prompt recognition and aggressive management of ARF in drowning victims. Early intubation and mechanical ventilation, along with supportive care, can lead to successful outcomes even in severe cases. This report emphasizes the importance of raising awareness about drowning prevention and the need for readily available emergency medical services to improve outcomes in such incidents.